The Diagnosis of Vocal Cord Movement Impairment Using Ultrasonography: A Comparison of Transthyroid and Suprathyroid Views - Mohseni, Masood; Alimian, Mahzad; Zaman, Behrouz; Faiz, Seyed Hamid Reza; Ahmadi, Sara; Koleini, Zahra Sadat (Annals of Anesthesiology and Critical Care, 2017)
Background: Iatrogenic recurrent laryngeal nerve (RLN) injury is an uncommon but serious iatrogenic complication, especially after head and neck surgeries, and some thoracic procedures. Laryngoscopy can be an invasive and uncomfortable procedure; therefore, the use of ultrasonography (US) as a noninvasive method of screening patients for impaired vocal cord mobility is desirable. This study was conducted to compare the visibility of vocal cords in 2 suggested US views: suprathyroid and transthyroid approaches. Methods: In this clinical trial, 144 patients of either sex, who were candidates for elective suchlike surgery, were enrolled. The participants underwent vocal cord US through transthyroid and suprathyroid windows in a transverse plane with and without water bath. The visibility of vocal cords in either view was graded from 1 (invisible) to 5 (clearly visible). Direct laryngoscopy was performed after surgeries, with anticipated risk of vocal cord dysfunction, in patients with suspicious or invisible vocal cords in US. Results: Symmetric movement of vocal cords was visible in 88.8% of the participants. The visibility of vocal cords in transthyroid view was better than the suprathyroid approach. The quality of sonographic views was better in females and in younger age groups. The application of water bath did not improve the overall visibility of vocal cords during US. Conclusions: Transthyroid US seem to be a valuable screening modality for anticipated vocal cord dysfunction. Application of this method, particularly in nonelderly women, conveys more favorable results. Future improvements in the ultrasound machines in the hands of well-trained clinicians will improve its diagnostic accuracy.